PREGI (PROGRAM EDUKASI GIZI DAN AKTIVITAS FISIK): PENINGKATAN PEMAHAMAN PERILAKU HIDUP SEHAT MELALUI GIZI SEIMBANG DAN AKTIVITAS FISIK BAGI ANAK SEKOLAH DASAR DI KOTA MATARAM - Angga, Prayogi Dwina; Makki, Muhammad; Putra, Gita Prima; Indraswati, Dyah (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2023)
This community service activity aims to provide a learning experience or create conditions for individuals, groups, and families by opening channels of communication, information, and education to improve knowledge, attitudes, and behaviors so that people are aware, willing, and able to practice clean living and healthy behaviors. The implementation method for this community service program is the presentation method in the classroom using Powerful Presentation Techniques (PPT) media and live demonstrations. Overall, learning and counseling for elementary school children about balanced nutrition and physical activity through empowering teachers and parents has great potential to change the lifestyle of Indonesian children. Cakranegara State Elementary School 39, as the party involved, has shown high enthusiasm for accepting the concept of balanced nutrition and physical activity, which is reflected in the implementation of education carried out for its students regarding balanced nutrition and physical activity.